N-Fluorobenzenesulfonimide: An Efficient Nitrogen Source for C–N Bond Formation - Li, Yan; Zhang, Qian (Synthesis, 2015)
N-Fluorobenzenesulfonimide, an efficient nitrogen source, has been successfully employed as a source of nucleophilic nitrogen or nitrogen radicals for the formation of C–N bonds. This review summarizes recent progress in this field.1 Introduction2 NFSI as a Source of Nucleophilic Nitrogen3 NFSI as a Source of Nitrogen Radicals4 Other Amination Reactions5 Conclusions
Keywords: nitrogenations; aminations; imidations; free radicals